Trichobezoars in Captive-Bred Fat-Tailed Dunnarts and Potential Preventative Protocols - Christine Moschos; Shari Cohen; Emily L. Scicluna; Stephen Frankenberg; Andrew J. Pask; Keshuan Chow (Veterinary Sciences)
Fat-tailed dunnarts (Sminthopsis crassicaudata) are an emerging model species for developmental, reproductive, and conservation biology research. Understanding their husbandry and enrichment needs is integral to ensuring best welfare in captive-bred populations. This was made evident following the sudden deaths of three dunnarts from a population housed at a university research facility between 2018 and 2022. Necropsy results revealed significant trichobezoars causing gastrointestinal obstruction. Following these findings, adjustments were made to the dunnart enclosures with the addition of autoclaved tree bark to capture loose fur as well as the inclusion of paraffin oil in the diet for the purpose of gastrointestinal lubrication. Since these husbandry interventions, no further deaths attributed to trichobezoars have been reported. Here, we present these data and outline new best practice methods for captive dunnart husbandry.